2018
DOI: 10.3390/en11010194
|View full text |Cite
|
Sign up to set email alerts
|

Impact on Congestion and Fuel Consumption of a Cooperative Adaptive Cruise Control System with Lane-Level Position Estimation

Abstract: Abstract:In recent years, vehicular communications systems have evolved and allowed for the improvement of adaptive cruise control (ACC) systems to make them cooperative (cooperative adaptive cruise control, CACC). Conventional ACC systems use sensors on the ego-vehicle, such as radar or computer vision, to generate their behavioral decisions. However, by having vehicle-to-X (V2X) onboard communications, the need to incorporate perception in the vehicle is drastically reduced. Thus, in this paper a CACC soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…Therefore, we consider the need to supplement cellular traffic information with cellular communications. The work in [6] provided long-distance transmissions using cellular communication systems, and an intelligent transportation system was realized by load-mapping and queuing theory, which can effectively cope with congestion problems. The work in [7], through analysis and simulation, showed that C-V2X-the technology developed within the third-generation Partnership Project (3GPP) and designed to operate in both vehicle-to-vehicle and vehicle-to-network modes-is the prominent technology that can achieve V2X requirements and pave the most efficient way to connected and automated driving.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we consider the need to supplement cellular traffic information with cellular communications. The work in [6] provided long-distance transmissions using cellular communication systems, and an intelligent transportation system was realized by load-mapping and queuing theory, which can effectively cope with congestion problems. The work in [7], through analysis and simulation, showed that C-V2X-the technology developed within the third-generation Partnership Project (3GPP) and designed to operate in both vehicle-to-vehicle and vehicle-to-network modes-is the prominent technology that can achieve V2X requirements and pave the most efficient way to connected and automated driving.…”
Section: Related Workmentioning
confidence: 99%
“…(5) The value-function sum of all sequences is the sequence value of the selection sequence. (6) The sequence with the highest value is the optimal selection sequence, and the base station of each vehicle in the sequence selects the best base station selection for the next second. To clearly describe the above mechanism, we provide an example in Figure 4.…”
Section: Markov Decision Policymentioning
confidence: 99%
“…These engines work most efficiently under a load of 80-85% of nominal power, and it is beneficial to create a situation where such a load is required to generate an appropriate amount of energy for the electric part of the drive system. In world literature, various analyzes [7], and methods [8][9][10] can be found, concerning the reduction of pollution emitted to the atmosphere by the internal combustion engines.…”
Section: Introductionmentioning
confidence: 99%
“…An example of these early works on their impact is a study on flow control and congestion management in Automated Highway Systems [31]. More recently, some real test analyses and simulations have shown that safety and energy efficiency can be significantly improved for the connected automated vehicle as well as for the neighbouring human-driven vehicles (e.g., [32][33][34]).…”
Section: Introductionmentioning
confidence: 99%